Daño ocasionado al banano por el murciélago Glossophaga soricina en el Valle de La Estrella, Limón, Costa Rica - Jiménez Jiménez, Jorge (1973)
Investigation of serious damage in the uppermost fingers of banana stems at Valle de la Estrella, Limón, Costa Rica, revealed that it was caused by nectarivorous hats of the species Glossophaga soririna. These bats clasp the newly opened banana flower to feed on the nectar, thus producing furrows of up to 6 mm deep in the first fingers with the claws of Iheir thumbs. This damage reached significant commercial proportions in 1970.Two farms in which Ihe proportion of damaged fruit was very high were selected for testing the two methods devised to control the bal population, capture of the animals in black nylon nets, and poisoning. Nectarivorous G. soricina bats captured in the nets were killed, those of other species were released. The first method was apparently more effective. With the reduction in the nectarivorous bat population, the consequent decrease in damaged fruit ceased to be a commercial problem.